Factors affecting Somatic Cell Count in milk of dairy cows in Costa Rica - Kline KE; Joyce F (International Journal of Veterinary Science and Research - Peertechz Publications, 2018)
Somatic cells, such as bacteria fi ghting leukocytes, are present in cow's milk as an immune response to combat intramammary infection. The primary objective of this study was to determine the effect of various factors on the somatic cell count, or SCC, within the milk of dairy cows. Factors studied in comparison to the SCC include the number of bacteria within the cows' milk, the age of the cows, the number of Hypoderma lineatum lesions on the cows, and the cows' diet and the sanitation practice at separate farms. Milk samples were collected from 13 cows from Farm 1, located in La Cruz, Costa Rica, 20 cows from Farm 2, located in La Cruz, Costa Rica, and 30 cows from Farm 3, located in Monteverde, Costa Rica. Farmers at each of these three farms fed their cows a slightly different diet, and carried out different procedures in relation to cleanliness during their milking process. The stage of lactation was kept constant to eliminate this confounding variable. Milk samples were observed for somatic cell and bacteria counts using a compound light microscope under 1000X magnifi cation using gel immersion. The fi ndings from this study indicate that somatic cells are signifi cantly correlated to bacteria in cow's milk, while somatic cells do not signifi cantly correlate with the cow's age or the number of H. lineatum lesions a cow has. This study also indicates that the sanitation practices and milking procedure that farmers use can affect their somatic cell counts, and that using a new and disposable cotton cloth or paper to wipe down the udders before milking may lead to lower somatic cell and bacteria counts than using the same wet rag to wipe down every cow. Also, treating the udders with a disinfectant before milking, instead of after, led to the lowest somatic cell and bacteria count.